Reductive splitting of hemicellulose with stable ruthenium-loaded USY zeolites. Issue 19 (11th July 2016) - Ennaert, Thijs; Feys, Simon; Hendrikx, Don; Jacobs, Pierre A.; Sels, Bert F.
Abstract : Precisely balancing of the location, amount and strength of the acid and metal function on a bifunctional zeolite catalyst is essential for selective sugar alcohol formation. Abstract : Reductive catalytic splitting to sugar alcohols is a promising technology to valorize (hemi)cellulosic feedstock. This contribution focuses on the conversion of arabinoxylan (AX), a common hemicellulose polymer, to pentitols like xylitol and arabitol in the presence of ruthenium-loaded H-USY zeolites. Both acid and metal sites on the catalyst play a crucial role in the bifunctional catalytic mechanism. Overall, the reaction mechanism involves hydrolysis of AX into shorter (less reactive) xylan oligomer intermediates (XOs), which are in turn hydrolysed into sugar monomers. The first step occurs fast in hot liquid water, but the second step which is rate limiting, requires acid catalysis. Literature has reported successful XO hydrolysis with soluble acids. However, USY zeolites, being non-corrosive instead of the former, are able to hydrolyse XOs more efficiently, likely due to their strong mesopore adsorption capacity. Once formed, the monomeric sugars should be hydrogenated on the metal sites as fast as possible, as otherwise undesired competitive acid catalysed side-reactions will occur. While another catalyst like Ru on carbon can also be used in the one-pot approach close proximity of the two sites, e.g. in the pores of the USY zeolite, is beneficial for the pentitol selectivity, as long as they are well harmonised. After searching for the ideal dual site balance, exceptionally high pentitol yields up to 90 mol% were achieved after only 5 h of reaction. Comparison with earlier reported cellulose reactions shows a narrowing of the ideal acid-to-metal range, besides a shift to lower ratios. Initial regeneration studies show a stable Ru/USY catalytic system able to perform multiple reaction runs with retention of activity and selectivity.